The Ultimum Remedium Paradigm in Corporate Bankruptcy and the Problem of Balancing Creditor Protection and Debtor Business Continuity - Tri Andika Syam; Boy Nurdin (Deposisi: Jurnal Publikasi Ilmu Hukum, 2026)
The development of modern bankruptcy law demonstrates a paradigm shift from solely liquidation mechanisms to an approach that places greater emphasis on business rescue and balancing the interests of the parties. The bankruptcy system in Indonesia, regulated by Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations, still tends to use bankruptcy as a rapid debt enforcement instrument, thus not fully reflecting the principle of ultimum remedium. This study aims to analyze the problem of balancing creditor protection with debtor business continuity and formulate a more proportional reconstruction of the bankruptcy paradigm. The research method used is normative legal research with statutory, conceptual, case, and comparative approaches. The analysis is conducted on the normative design of bankruptcy, the strategic practices of the use of bankruptcy petitions by creditors, the ambivalence of judicial discretion, and the inequality of protection between creditors and debtors. The results of the study indicate that the relatively simple requirements for bankruptcy petitions and the absence of a screening mechanism for business feasibility contribute to the tendency for premature liquidation. The existing paradigm is still dominated by a creditor enforcement orientation, thus suboptimal business restructuring opportunities. Reconstructing the bankruptcy paradigm requires positioning bankruptcy as an instrument of ultimum remedium through an escalation model, prioritizing restructuring before liquidation, and implementing the principle of proportionality in judicial practice. Normative reforms are proposed through strengthening the PKPU mechanism as a first remedy, reformulating the bankruptcy threshold, and developing a judicial balancing test that balances legal certainty with economic sustainability. This approach is expected to create a bankruptcy system that is more adaptive, fair, and aligned with the needs of the modern economy.